Analisis Filosofis: Pemikiran Abu Ubaid dalam Kitab Al-Amwal - Rahmah, Zakiyah Zulfa; Samsuri , Ali (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
This article reviews the concept of Islamic economics related to the role of money according to the thought of Abu Ubaid (154-224 AH). In his work, Kitab Al-Amwal, Abu Ubaid highlights the importance of justice as a fundamental principle. Although written in the past, Abu Ubaid's ideas remain relevant in the current economic and social context, especially in efforts to maintain fairness in wealth distribution and transparency in public financial management. Money in Abu Ubaid's view has a dual role, as a standard and medium of exchange. The principles advocated by Abu Ubaid can be valuable guidelines for policy makers in designing an inclusive and sustainable economic system. Thus, an understanding of Abu Ubaid's thought can provide valuable insights in the development of a just and efficient Islamic economy.